2014
DOI: 10.1182/blood-2013-10-534743
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag restores trilineage hematopoiesis in refractory severe aplastic anemia that can be sustained on discontinuation of drug

Abstract: Key Points Eltrombopag promotes hematopoiesis in patients with severe aplastic anemia by stimulating stem and progenitor cells. Eltrombopag can be discontinued safely in robust responders with maintenance of hematopoiesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
371
10
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(408 citation statements)
references
References 45 publications
14
371
10
5
Order By: Relevance
“…These results compare favorably with the results reported for drug therapy for patients with refractory SAA, with responses rates in the range of 30-50% for most therapeutic options. 6,7,9,10 In the past, the use of haploidentical donors was limited by the incidence of severe GVHD and the need for profound ex vivo T-cell depletion, which impaired immune reconstitution and contributed to an increased risk of infections, relapse and non-relapse mortality. Post-transplant Cy is an effective strategy for GVHD prevention with reduced impairment in immune reconstitution that is observed with more profound T-cell depletion strategies previously used in haploidentical HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results compare favorably with the results reported for drug therapy for patients with refractory SAA, with responses rates in the range of 30-50% for most therapeutic options. 6,7,9,10 In the past, the use of haploidentical donors was limited by the incidence of severe GVHD and the need for profound ex vivo T-cell depletion, which impaired immune reconstitution and contributed to an increased risk of infections, relapse and non-relapse mortality. Post-transplant Cy is an effective strategy for GVHD prevention with reduced impairment in immune reconstitution that is observed with more profound T-cell depletion strategies previously used in haploidentical HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Current therapeutic strategies for these patients include a higher risk hematopoietic stem cell transplantation (HSCT) from mismatched donors, a second course of immunosuppression, androgens, and more recently, the TPO receptor agonist eltrombopag recently approved in this setting. 3,[6][7][8][9][10] Higher risk HSCT for those who lack a histocompatible donor often include umbilical cord blood and haploidentical donor as a source of HSCs (HSCs). [11][12][13][14][15][16][17][18][19] The use of haploidentical donors has some advantages compared with matched unrelated donors (MUD) and cord blood units, as a donor is more widely and readily available usually within the family, abbreviating the time for stem cell collection and infusion into the recipient.…”
Section: Introductionmentioning
confidence: 99%
“…Five patients were subsequently able to stop eltrombopag and have maintained stable blood counts despite stopping the drug at a median of 13 months off eltrombopag (range, 1-15 months). 16 One concern about the use of the use of eltrombopag is the potential for clonal evolution. Eight of 43 patients (19%) developed new and early cytogenetic abnormalities, most by 3 months (range, 3-13 months) and most often monosomy 7.…”
Section: How Can We Improve the Response To Immune Suppressive Therapy?mentioning
confidence: 99%
“…However, the clonal evolution rate of 19%, as reported in initial eltrombopag studies, is similar both to our current analysis and to that reported in refractory SAA. 5,9,12,14,15 Ongoing studies employing eltrombopag in combination with h-ATG/CsA as first therapy will further elucidate the clonal evolution risk.…”
Section: T O R T I F O U N D a T I O Nmentioning
confidence: 99%
“…It has recently been shown that eltrombopag induces hematologic response in up to 44% of refractory SAA patients, which included trilineage responses.14 This was expanded to a larger cohort with longer follow-up which confirmed the response rate of about 40%, and multilineage increments in blood counts were again observed. 15 One of the concerns related to rescue eltrombopag is the potential propensity to stimulate clonal evolution. However, the clonal evolution rate of 19%, as reported in initial eltrombopag studies, is similar both to our current analysis and to that reported in refractory SAA.…”
Section: T O R T I F O U N D a T I O Nmentioning
confidence: 99%